Paramedics and emergency medical technicians’ perceptions of geriatric trauma care in Saudi Arabia - Naif Harthi; Steve Goodacre; Fiona C. Sampson; Meshary Binhotan; Abdullah Suhail Alotaibi (BMC Emergency Medicine)
Abstract Background Saudi ambulance clinicians face unique challenges in providing prehospital care to older trauma patients. Limited geriatric-specific training and complex needs of this population hinder effective management, leading to adverse outcomes. This study explores the perceptions of Saudi ambulance clinicians regarding geriatric trauma care and identify facilitators and barriers to improved care. Methods A qualitative study was conducted using a purposive sample of Saudi paramedics and ambulance technicians from Riyadh and Makkah using online semi-structured interviews and analysed using the framework method. Results The qualitative study recruited twenty participants and identified that they reported age-related challenges including physiological changes, polypharmacy, and communication difficulties. They all wanted training and guidelines to improve their knowledge. They reported struggling with communication difficulties, inaccurate adverse outcomes predictions, difficult intravenous cannulations, and cultural restrictions affecting care provision for female patients. We identified organisational barriers (e.g. lack of shared patient records and lack of guidelines) and cultural barriers (e.g. barriers to assessing women, attitudes towards older people, and attitudes towards paramedics) that influenced implementation of knowledge. Conclusion Ambulance clinicians in Saudi Arabia want guidelines and training in managing older trauma patients but these need to take into account the organisational and cultural barriers that we identified to facilitate implementing knowledge and changing practice to providing improved care.